Development of diagnostic methods and study of the immunoreactivity of a mixture of recombinant core and E2 proteins fused to GST with control serum positive for hepatitis C - Kenfe, Flavia Regina [UNESP]; Urbaczek, Ana Carolina [UNESP]; Silva, Juliana Cristina [UNESP]; Neo, Thalita Athie [UNESP]; Silva, Flavio Henrique da; Costa, Paulo Inácio da [UNESP] (Elsevier B.V., 2013)
The hepatitis C virus (HCV) is an enveloped virus that is about 50-70 nm in diameter, has positive-strand RNA, and belongs to the genus Hepacivirus and the family Flaviridae. The detection and quantification of the core antigen, HCV nucleocapsid protein, has been successful in many trials and is considered a marker of viral replication since it presents a sequence of highly conserved amino acids, giving it high sensitivity and specificity. The E2 protein is an envelope glycoprotein of HCV with 11 glycosylation sites; most of these are well-conserved, making it a target antigen. The aim of this study is to develop high-sensitivity, low-cost diagnostic methods for HCV, which could be used for serological screening. The genomic regions encoding the core (part 136 aa) and E2 proteins of HCV were expressed in Escherichia coli Rosetta strain, cloned in expression vector pET-42a, and induced with 0.4 mmolL(-1) IPTG, producing recombinant proteins that were fused to glutathione S-transferase (GST) protein, which was then purified by affinity chromatography. The immunoreactivity was assessed by Western blot, Slot Blot, and developed and improved diagnostic methods (capture, indirect, and immunoblotting enzyme-linked immunosorbent assay (ELISA)). After applying the results to the formulas for determining the quality parameters, obtained for immunoblotting method 100% sensitivity and specificity and for ELISA 100% sensitivity and 87.5% specificity. The methods developed were more sensitive and specific using the mixture of the recombinant proteins fused to GST (core+E2). (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Hepatitis C virus; GST-core protein; GST-E2 protein; Capture ELISA; Indirect ELISA; Immunoblotting